2010
DOI: 10.3844/jcssp.2010.1406.1415
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Mashup as a Software Application Development Technique with Examples from an End-User Programming Perspective

Abstract: Abstract:The purpose of this study is to present, introduce and explain the principles, concepts and techniques of mashups through an analysis of mashup tools from End-user Development (EuD) software engineering perspectives, since it is a new programming paradigm. Problem statement: Although mashup tools supporting the creation of mashups rely heavily on data integration, they still require users to have reasonable programming skills, rather than simply enabling the integration of content in a template approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Although perceptions of security and privacy protection are likely to differ according to each user's, traditions, culture, social networking and other factors, web site design and content elements can exchange privacy credentials to ensure user information is protected. With regard to design, site complexity and layout for presence and number of hyperlinks, obtrusiveness of advertising, ease of navigation, and general professionalism have been shown to affect perceptions about the authority of the site (Na et al, 2010). Perceptions on the site's authority may impact the user's privacy perception of the site.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although perceptions of security and privacy protection are likely to differ according to each user's, traditions, culture, social networking and other factors, web site design and content elements can exchange privacy credentials to ensure user information is protected. With regard to design, site complexity and layout for presence and number of hyperlinks, obtrusiveness of advertising, ease of navigation, and general professionalism have been shown to affect perceptions about the authority of the site (Na et al, 2010). Perceptions on the site's authority may impact the user's privacy perception of the site.…”
Section: Introductionmentioning
confidence: 98%
“…Mashup is an exciting interactive web application that draws upon diverse content retrieved from external data sources to create entirely new and innovative meta-application services (Na et al, 2010). Although mashup implies "unstructured" by definition, it is organized, serving as a weaver that systematically aggregates and stitches together third-party data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several architectures exist for CC, which behaves differ in what kind of computing services are offered to this environment, culminating with the advances with Web 3.0 and Web 4.0 technologies [1]. Detailed studies of different approaches to CC can be found in [2] [3].…”
Section: Introductionmentioning
confidence: 99%
“…automatic description generation for composites), or further investigation of the design space for EUSC tools. Given the apparent popularity of design space research in EUSC and mashup tools [25,[31][32][33], this seems to be a promising avenue for requirements validation.…”
Section: Limitations and Future Workmentioning
confidence: 99%